IMPROVEMENT OF TEACHER SCHOOL COMPETENCIES THROUGH TEACHER PERFORMANCE MANAGEMENT, ORGANIZATIONAL CULTURE, SELF-DEVELOPMENT, WORK MOTIVATION, AND INTERPERSONAL SKILLS IN YOGYAKARTA CITY - Agus Sutikno, Sugiyono, Udik Budi Wibowo, Sugeng Widarso (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the relationship model of a variable that affects teacher competencies, to measure the direct and indirect effects of teacher performance management, organizational culture, self-development, work motivation, and interpersonal skills on elementary school teacher competencies at Yogyakarta city, and to measure the influence of variables that affect teacher competencies.